2008
DOI: 10.1159/000113709
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at the Paraoxonase 1 L55M and Q192R Loci Affect the Pathophysiology of Alzheimer’s Disease: Emphasis on the Cholinergic System and Beta-Amyloid Levels

Abstract: Background: Paraoxonase 1 (PON1) functions to protect the cholinergic system against nerve gases and the organophosphate family of pesticides. Recent studies have shown that polymorphisms at the PON1 L55M and Q192R loci might affect individual susceptibility to experience-derived and environmental events such as the exposure to inhibitors of cholinesterase (ChEIs). Objective: ChEI therapy being the treatment of choice for mild-to-moderate Alzheimer’s disease (AD) patients, we determined whether genetic variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…The association of PON1 gene polymorphism and risk of certain diseases has been documented (Sidoti et al, 2007;Leduc and Poirier, 2008;Agrawal et al, 2009;Leduc et al, 2009). In addition, PON1 gene polymorphisms (Q192R, L55M) alter both the level and activity of the enzyme (Humbert et al, 1993;Garin et al, 1997;Mackness et al, 1998;Aviram et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…The association of PON1 gene polymorphism and risk of certain diseases has been documented (Sidoti et al, 2007;Leduc and Poirier, 2008;Agrawal et al, 2009;Leduc et al, 2009). In addition, PON1 gene polymorphisms (Q192R, L55M) alter both the level and activity of the enzyme (Humbert et al, 1993;Garin et al, 1997;Mackness et al, 1998;Aviram et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…97 Multiple studies have addressed the association between PON1 polymorphisms and AD. 91,[98][99][100][101][102][103][104][105] In a study with 756 AD subjects, the authors found no association between the two major PON1 polymorphisms and AD in African Americans or Caucasians. 91 The authors conclude that either these functional PON1 polymorphisms are not associated with AD, or that the relative risk is small.…”
Section: 70-73mentioning
confidence: 93%
“…[25][26][27]92,94 In a large study with an over 1000 cohort of clinical and autopsy-confirmed AD cases and age-matched, cognitively intact controls, multiple gender-specific effects of PON1 polymorphisms on AD pathogenesis were apparent. 101 The L55M…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who developed dementia were found to have a higher frequency of the 55M allele (91)(92). Although Helpecque et al reported that the -107T allele meant high risk of dementia (93), it was concluded in another study that this observation was a contradiction (94).…”
Section: Clinical Significancementioning
confidence: 96%